Interactive Storytelling and Prosocial Helping Skills among Early Childhood Learners - Rista Erika; Fitri Novia Fizriah; Nadya Pharda S; Syifa; Zahra Nabila (PT Nawa Edukasi Nusantara, 2026)
Prosocial helping skills are an important part of early childhood social-emotional development. However, these skills do not always receive balanced attention in classroom practice because learning activities often focus more on academic achievement. This study aimed to examine the relationship between interactive storytelling and children’s prosocial helping skills at RA Nasyidul Ummi. The study used a quantitative correlational approach. The population consisted of 15 children, and all children were selected as the sample through total sampling. Data were collected using a structured observation sheet consisting of 6 items for interactive storytelling and 6 items for prosocial helping skills. The data were analyzed using descriptive statistics, validity testing, reliability testing, normality testing, linearity testing, correlation analysis, and simple linear regression. The results showed that the mean score of interactive storytelling was 15.20, while the mean score of prosocial helping skills was 14.80. The Pearson correlation was 0.948 and the Spearman correlation was 0.960, with a significance value of 0.000. Simple linear regression produced the equation Y = 2.519 + 0.808X, with an R Square value of 0.900. These findings indicate that interactive storytelling has a very strong positive relationship with children’s prosocial helping skills. Interactive storytelling can be used as a social learning strategy to help children develop care, helping behavior, sharing, and cooperation with peers.